2018
DOI: 10.1097/01.ogx.0000549835.38093.d4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes After Elective Sterilization Procedures—A Comparative Retrospective Cohort Study of Medicaid Patients

Abstract: The objectives were to compare the long-term outcomes, including hysterectomy, chronic pelvic pain (CPP) and abnormal uterine bleeding (AUB), in women post hysteroscopic sterilization (HS) and laparoscopic tubal ligation (TL) in the Medicaid population. Study design: This was a retrospective observational cohort analysis using data from the US Medicaid Analytic Extracts Encounters database. Women aged 18 to 49 years with at least one claim for HS (=3929) or TL (= n n 10,875) between July 1, 2009, through Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The characteristics and results of all included studies can be found in Table 1. Six studies compared effectiveness [34][35][36][37][38][39]; 15 assessed adverse effects [17,18,34,35,[38][39][40][41][42][43][44][45][46][47][48]; three compared patient recovery [18,35,44]; five compared non-contraceptive benefits, primarily the reduction of cancer risk [43,[49][50][51][52]; six compared tolerability [34,35,[37][38][39]52]; four compared costs to the healthcare system; [38,[53][54][55] and seven compared length of procedures [17,18,38,44,47,48,55]. No included studies compared accessibility, eligibility, or follow-up required.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The characteristics and results of all included studies can be found in Table 1. Six studies compared effectiveness [34][35][36][37][38][39]; 15 assessed adverse effects [17,18,34,35,[38][39][40][41][42][43][44][45][46][47][48]; three compared patient recovery [18,35,44]; five compared non-contraceptive benefits, primarily the reduction of cancer risk [43,[49][50][51][52]; six compared tolerability [34,35,[37][38][39]52]; four compared costs to the healthcare system; [38,[53][54][55] and seven compared length of procedures [17,18,38,44,47,48,55]. No included studies compared accessibility, eligibility, or follow-up required.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The characteristics and results of all included studies can be found in Table 1. Of the studies included for the narrative synthesis, six compared effectiveness; [24][25][26][27][28][29] sixteen assessed adverse effects; 11,24,25,[28][29][30][31][32][33][34][35][36][37][38][39][40] three compared patient recovery; 25,35,36 ve compared non-contraceptive bene ts, primarily the reduction of cancer risk; 34, 41-44 six compared tolerability; 24,25,[27][28][29]44 four compared costs to the healthcare system; 28,[45][46][47] and six compared length of procedures. 11,28,35,36,40,47 No included studies compared accessibility, eligibility, or follow-up required.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sixteen studies assessed adverse effects using prospective/retrospective cohort designs. Results are organized by intervention: six compared hysteroscopic tubal occlusion and laparoscopic tubal ligation, 24,25,[28][29][30][31] three compared laparoscopic tubal ligation and a control, [32][33][34] ve compared laparoscopic tubal ligation and bilateral salpingectomy, 11,[35][36][37]40 one compared hysteroscopic tubal occlusion, laparoscopic tubal ligation with controls, and bilateral salpingectomy with controls, 38 and one compared bilateral salpingectomy with laparoscopic tubal ligation and with matched controls. 39 Hysteroscopic tubal occlusion vs. Laparoscopic tubal ligationTwo studies 24,30 found no statistically signi cant difference in rates of adverse effects including abnormal uterine bleeding, pelvic pain, or opioid managed pain between the two interventions.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 2 more Smart Citations